Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischemic Stroke: Primary Results of the STRATIS Registry. Issue 10 (October 2017) - Mueller-Kronast, Nils H.; Zaidat, Osama O.; Froehler, Michael T.; Jahan, Reza; Aziz-Sultan, Mohammad Ali; Klucznik, Richard P.; Saver, Jeffrey L.; Hellinger, Frank R.; Yavagal, Dileep R.; Yao, Tom L.; Liebeskind, David S.; Jadhav, Ashutosh P.; et al.
Abstract : Background and Purpose—: Mechanical thrombectomy with stent retrievers has become standard of care for treatment of acute ischemic stroke patients because of large vessel occlusion. The STRATIS registry (Systematic Evaluation of Patients Treated With Neurothrombectomy Devices for Acute Ischemic Stroke) aimed to assess whether similar process timelines, technical, and functional outcomes could be achieved in a large real world cohort as in the randomized trials. Methods—: STRATIS was designed to prospectively enroll patients treated in the United States with a Solitaire Revascularization Device and Mindframe Capture Low Profile Revascularization Device within 8 hours from symptom onset. The STRATIS cohort was compared with the interventional cohort of a previously published SEER patient-level meta-analysis. Results—: A total of 984 patients treated at 55 sites were analyzed. The mean National Institutes of Health Stroke Scale score was 17.3. Intravenous tissue-type plasminogen activator was administered in 64.0%. The median time from onset to arrival in the enrolling hospital, door to puncture, and puncture to reperfusion were 138, 72, and 36 minutes, respectively. The Core lab–adjudicated modified Thrombolysis in Cerebral Infarction ≥2b was achieved in 87.9% of patients. At 90 days, 56.5% achieved a modified Rankin Scale score of 0 to 2, all-cause mortality was 14.4%, and 1.4% suffered a symptomatic intracranial hemorrhage. The median time from emergency medical services scene arrival to puncture was 152 minutes, and each hour delay in this interval was associated with a 5.5% absolute decline in the likelihood of achieving modified Rankin Scale score 0 to 2. Conclusions—: This largest-to-date Solitaire registry documents that the results of the randomized trials can be reproduced in the community. The decrease of clinical benefit over time warrants optimization of the system of care. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02239640. Abstract : Supplemental Digital Content is available in the text.